2017
DOI: 10.1155/2017/9450439
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor 9 Promotes Survival in SERCA2a KO Heart Failure Mice

Abstract: Aim. Inflammation is important in heart failure (HF). The role of the immune receptor toll-like receptor 9 (TLR9) in HF is not understood and not investigated in diastolic HF. We investigated the role of TLR9 in a murine diastolic HF model caused by cardiomyocyte SERCA2a excision. Methods and Results. We crossed SERCA2a KO and TLR9 KO mice to generate four mouse lines. Tamoxifen-induced cardiomyocyte SERCA2a gene excision was carried out in mice, causing diastolic HF. After 7.6 weeks, cardiac functions and dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Dhondup et al [ 94 ] reported that in a mouse model with diastolic HF caused by cardiomyocyte-specific deletion of SERCA2a, sustained activation of TLR9 caused cardiac and systemic inflammation and deterioration of SERCA2a depletion-mediated diastolic HF. In another diastolic HF mouse model induced by cardiomyocyte-specific deletion of SERCA2a, TLR9 depletion in those models reduced the survival rate compared with that of the SERCA2a KO control mice; this finding indicates the salutary role of TLR9 in some subsets of HF [ 95 ]. These studies suggest a link between systemic TLR9 activation and diastolic HF.…”
Section: Tlr Signaling and Hfmentioning
confidence: 99%
“…Dhondup et al [ 94 ] reported that in a mouse model with diastolic HF caused by cardiomyocyte-specific deletion of SERCA2a, sustained activation of TLR9 caused cardiac and systemic inflammation and deterioration of SERCA2a depletion-mediated diastolic HF. In another diastolic HF mouse model induced by cardiomyocyte-specific deletion of SERCA2a, TLR9 depletion in those models reduced the survival rate compared with that of the SERCA2a KO control mice; this finding indicates the salutary role of TLR9 in some subsets of HF [ 95 ]. These studies suggest a link between systemic TLR9 activation and diastolic HF.…”
Section: Tlr Signaling and Hfmentioning
confidence: 99%
“…28 Moreover, the role of TLR9 has been implicated in several animal studies of cardiovascular diseases including myocardial infarction, [29][30][31] myocardial ischaemia/reperfusion injury, 32 atherosclerosis 33,34 and heart failure. 35,36 Elevated plasma levels of mtDNA have also been reported in patient studies associated with increased mortality and cardiac inflammation. 20,37 In our study, the amount of circulating mtDNA increased following MI and lower pro-inflammatory cytokine expression was observed in MAIR-II-deficient BMDMs stimulated by a TLR9 agonist.…”
Section: Discussionmentioning
confidence: 92%
“…Once NF‐κB is activated, pro‐inflammatory cytokine transcription is up‐regulated 28 . Moreover, the role of TLR9 has been implicated in several animal studies of cardiovascular diseases including myocardial infarction, 29‐31 myocardial ischaemia/reperfusion injury, 32 atherosclerosis 33,34 and heart failure 35,36 . Elevated plasma levels of mtDNA have also been reported in patient studies associated with increased mortality and cardiac inflammation 20,37 .…”
Section: Discussionmentioning
confidence: 99%
“…TLR9 can also prevent cardiac rupture after myocardial infarction [33]. Knockout of TLR9 in the sarcoplasmic/endoplasmic reticulum Ca2+ ATPase 2a (SERCA2a) diastolic heart failure mice reduces their survival [34]. However, ablation of TLR9 in mice attenuates myocardial ischemia injury [35].…”
Section: Discussionmentioning
confidence: 99%